Pengaruh Permainan Kartu Ngaji Asyik Terhadap Kemampuan Mengenal Huruf Hijaiyah Anak - Wirman, Asdi; Yanni, Rizka Putri (Universitas Negeri Padang, 2023)
This studyaaims to determinenthe effect offfun recitation card games on children's ability torrecognize hijaiyahlletters in Kartika Kindergarten 1-61 Padang. The lack of development of children's ability to recognize hijaiyah letters, this is caused by the lack of variety of games or media used so that children get bored easily and are not interested in knowing hijaiyah letters. Thissstudy uses a quantitative method with a quasy experimental method. The sampling technique in this study used a total sampling techniquenwhere the entire populationnwas sampled, namely the experimental class, which consisted of 10 people and the control class, 9 children. In this study, the datananalysismtechniques used were the normality test, homogeneityltest and hypothesis testing. In this test, significant results were obtained from the hypothesis test (t-test) with a tailed Sig.2 valuelof 0.000<0.005, which means that there is an influence from the fun recitation card game on the abilitylto recognize children's hijaiyahlletters and it is stated that Ha is accepted while Holis rejected.